Diffusion-Weighted Lesions After Intracerebral Hemorrhage: Associated MRI Findings - Wiegertjes, Kim; Voigt, Sabine; Jolink, Wilmar M. T.; Koemans, Emma A.; Schreuder, Floris H. B. M.; van Walderveen, Marianne A. A.; Wermer, Marieke J. H.; Meijer, Frederick J. A.; Duering, Marco; de Leeuw, Frank-Erik; Klijn, Catharina J. M. (Frontiers in Neurology, 2022)
To investigate whether diffusion-weighted imaging-positive (DWI+) lesions after acute intracerebral haemorrhage (ICH) are associated with underlying small vessel disease (SVD) or linked to the acute ICH. We included patients ≥18 years with spontaneous ICH confirmed on neuroimaging and performed 3T MRI after a median of 11 days (interquartile range [IQR] 6-43). DWI+ lesions were assessed in relation to the hematoma (perihematomal vs. distant, and ipsilateral vs. contralateral). Differences in clinical characteristics, ICH characteristics and MRI markers of SVD between participants with or without DWI+ lesions were investigated using non-parametric tests. We observed 54 DWI+ lesions in 30 (22%) of the 138 patients (median age [IQR] 65 [55-73] years; 71% male, 59 lobar ICH) with available DWI images. We found DWI+ lesions ipsilateral (54%) and contralateral (46%) to the ICH, and 5 (9%) DWI+ lesions were located in the immediate perihematomal region. DWI+ lesion presence was associated with probable CAA diagnosis (38% vs 15%, p = .01) and larger ICH volumes (37 [8–47] vs 12 [6-24] mL, p=.01), but not with imaging features of SVD. Our findings suggest that DWI+ lesions after ICH are a feature of both the underlying SVD and ICH-related mechanisms.